Protection of minorities victims of armed conflicts in light of international humanitarian law: Women and children of the minority as a model - HADDAD, Rania (Journal of Human Sciences, 2025)
International humanitarian law aims to protect civilians in general during armed conflicts, including minorities. These groups are often subjected to a wide range of serious violations of human rights, both in general and specifically as minorities, such as genocide, forced displacement, and other unlawful aggressive practices. Consequently, international humanitarian law imposes a duty to protect civilians against all parties involved, under any circumstances during armed conflicts, especially women and children. However, the reality faces significant challenges in realizing the content of this legal protection afforded to minorities. Therefore, the international community seeks to focus protection on these specific groups through international and regional mechanisms. This research paper will discuss the conceptual framework of armed conflicts and the groups concerned with protection, and then move on to highlight the international legal framework for protecting these groups, relying on both descriptive and analytical approaches.